Pengembangan Sistem Informasi Pejabat Pengelola Informasi dan Dokumentasi Kabupaten Solok Selatan berbasis Website - Ikhsan Khaliq; Fajar Pradana; Buce Trias Hanggara (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
The transparency of Information is one of the important characteristic of a democratic country. Therefore, every individual should be able to obtain information in an easy way, one of which is public information that is useful for maintaining harmonious relations between the government and society. transparency of public information is one of the government's central roles in terms of fulfilling the rights of individuals or groups to be able to obtain public information when needed. The public institution that provides and serves requests for public information is called the Information and Documentation Management Officer or PPID. PPID is responsible for storing, documenting and providing services on public information. In PPID of South Solok Regency, one of the main problems is that activities about services provided by PPID of South Solok Regency are not being carried out in the PPID information system that has resulted to slow response towards any activities because there is no notification of those activities. Furthermore, some other problems are public information cannot be downloaded and the images on the website do not appear. Based on the problems, PPID of South Solok Regency suggested to development a new web-based information system. The development of the new information system for South Solok Regency employs one of the SDLC methods, which is the waterfall method. This information system was developed mainly using the Laravel framework and MySQL database, and several JavaScript libraries to support the development of this system. This research is expected to be able to solve the problems that exist in the PPID of South Solok Regency and to make it easier for users to use the PPID services.